The european social model and the shortcomings of the active welfare state (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Since 2008, the European Union, and especially the Eurozone, is hit by a deep economic crisis that translates into rising unemployment, rising povertyrates, and rising inequalities. Even if some countries, like Italy, Greece, Portugal, and Spain, face more serious social challenges than others, similar trends occuralmost everywhere. However, we should remember that even before the crisis the social situation was deteriorating in many European countries, despite the fact that an “open method of coordination” (OMC) on social inclusion had been launched by the European Commission in 2000. Of course, one could hardly deny the fact that the crisis actually amplifies these social problems. In this paper, I will nevertheless argue that it would be too simplistic to have an exclusive focus on the current economic downturn. Indeed, in order to think about new welfare strategies, we need to look at what has failed in the policies that have been designed so far. When they doso, an increasing number of researchers now conclude that some of the social policies that were implemented during the 2000s, i.e. during the first decade ofthe OMC on social inclusion, had a very limited impact – or even a negative impact – on social justice across Europe.3 My modest aim is to look at some ofthese policies, first at a general level (section 1), and second at a more specific level, through some illustrative examples in one member-state, Belgium (section2). The following sections are not based on first-hand research, but are rather aimed at reviewing the most interesting features of the current academicdiscussion in Belgium. The paper relies especially – although not exclusively – on research conducted by experts at Belgium’s most advanced research centrein social policy, the Herman Deleeck Centre for Social Policy at the Universityof Antwerp.
Keywords: European Social model; activation policies; Welfare State; redistribution; unemployment